Autofluorescence-based high-throughput isolation of nonbleaching Cyanidioschyzon merolae strains under nitrogen-depletion - Takeue, Nozomi; Kuroyama, Ayaka; Hayashi, Yoshiharu; Tanaka, Kan; Imamura, Sousuke (Frontiers in Plant Science, 2022)
Photosynthetic organisms must maintain optimum levels of photosynthetic pigments in response to environmental conditions, both for survival and to regulate growth. The identification of cyanobacteria strains that alleviate bleaching has revealed genes that regulate pigment levels. In contrast, the mechanisms of pigment degradation in algae remain unclear, as no nonbleaching strains have previously been isolated. To address this issue, this study attempted to isolate nonbleaching strains of the unicellular red alga Cyanidioschyzon merolae after exposure to nitrogen (N)-depletion based on autofluorescence information. After four weeks under N-depletion, 13 cells from 500,000 cells with almost identical pre- and post-depletion chlorophyll a (Chl a) and/or phycocyanin autofluorescence intensities were identified. These nonbleaching candidate strains were sorted via a cell sorter, isolated on solid medium, and their post-N-depletion Chl a and phycocyanin levels were analyzed. As seen in the control strain, their Chl a levels were lower at 1–4 weeks of N-depletion, however, their phycocyanin levels were unchanged. Thus, we successfully isolated nonbleaching C. merolae strains in which phycocyanin was not degraded under N-depletion, via autofluorescence spectroscopy and cell sorting. This versatile method will help to elucidate the mechanisms regulating pigments in microalgae.